ORGANIC FOOD MARKET IN JAVA AND BALI: CONSUMER PROFILE AND MARKETING CHANNEL ANALYSIS - Mukhamad Najib; Ujang Sumarwan; Stevia Septiani (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2020)
Abstrak Tren keamanan pangan menjadi isu sensitif dalam industri pangan saat ini. Pertanian organik dapat menjadi alternatif solusi karena memiliki keseimbangan lingkungan, kesehatan, dan kebermanfaatan bagi petani lokal. Namun, tingginya harga produk serta skala produksi yang masih rendah menjadi faktor yang membatasi pertumbuhan pasar pangan organik di dalam negeri. Penelitian ini bertujuan menganalisis perilaku konsumen pangan organik, menganalisis saluran pemasaran dan memformulasikan alternatif saluran pemasaran pangan organik dalam negeri. Pengambilan sampel dilakukan secara purposive dimana kriteria responden adalah mereka yang mengetahui pangan organik dan berdomisili di lima kota besar pulau Jawa dan Bali. Survei saluran pemasaran dilakukan di Jakarta dan Jawa Barat dengan mewawancarai aktor-aktor di setiap rantai nilai. Hasil penelitian menunjukkan peluang pasar pangan organik cukup besar, karena umumnya responden telah menyadari bahwa pangan organik baik untuk kesehatan. Konsumen pangan organik saat ini termasuk kelompok middle class segment berusia 20-50 tahun, pekerja kantoran dan berpenghasilan di atas Rp 9 juta. Bagi konsumen, label sertifikasi pangan organik lebih penting dari merek. Saluran pemasaran organik sangat bervariasi. Pada pasar B2C pemanfaatan digital marketing dapat meminimalisir risiko finansial petani organik. Sementara pasar B2B dapat dioptimalkan melalui kerjasama perhotelan, restoran, kafe, rumah sakit, dan industri pengolahan makanan sehat, serta didukung kebijakan pemerintah yang selaras. Kata Kunci: Pangan Organik, Perilaku Konsumen, Saluran Pemasaran, Negara Berkembang Abstract The trend of food safety is a sensitive issue in the food industry today. Organic agriculture can be an alternative solution because it has a right balance in terms of the environment, health and benefits for local farmers. However, high prices for organic products and low production scale limit the growth of the domestic organic food market. This research aims to analyze organic food’s consumer behavior, analyze the existing marketing channels and formulate alternative marketing channels for the domestic organic food supply chain. Sampling was carried out by purposive sampling method in which the criteria for respondents were those who know about organic food and live in five big cities in Java and Bali. The marketing channel survey was conducted in Jakarta and West Java by interviewing each actor in the value chain. The results showed that organic food’s market opportunity was quite large, because the respondents were generally aware that organic food was good for health. Organic food consumers are currently included in the middle-class segment, aged 20-50 years, office workers, and income more than IDR 9 million a month. For consumers, certification labels are more important than brands in organic food. On the one hand, organic marketing channels still vary widely. In the B2C market, the use of digital marketing can minimize the financial risks of organic farmers. On the other hand, the B2B market can be optimized through cooperation in hotels, restaurants, cafes, hospitals, and the healthy food processing industry, supported by government policies. Keywords: Organic Food, Consumer Behavior, Marketing Channels, Developing Countries JEL Classifications: D11, F10, F18